Disparities in behavioral health and experience of violence between cisgender and transgender Thai adolescents. - Wit Wichaidit; Sawitri Assanangkornchai; Virasakdi Chongsuvivatwong (PLoS ONE)
Background The term "transgender" refers to an individual whose gender identity is different from their sex assigned at birth, whereas the term "cisgender" refers to an individual whose gender identity is the same as their sex assigned at birth. In Thailand, studies on health outcomes and quality of life of Thai transgender youths have not included assessments from nationally-representative samples. The objective of this study is to assess the extent that behavioral health outcomes and exposure to violence varied by gender among respondents of the National School Survey on Alcohol Consumption, Substance Use and Other Health-Risk Behaviors. Methods We used data from a nationally-representative self-administered survey of secondary school students in years 7, 9 and 11 and classified participants as cisgender boys, cisgender girls, transgender boys, and transgender girls. Participants also answered questions on depressive experience, suicidality, sexual behaviors, alcohol and tobacco use, drug use, and past-year experience of violence. We analyzed data using descriptive statistics and modified multivariate Poisson regression with adjustment for sampling weights to calculate adjusted prevalence ratios (APR) with 95% confidence intervals. Results A total of 31,898 respondents (82.8% of those who returned complete and valid questionnaires) answered questions on sex and gender identity and were included in the analyses (n = 31,898 respondents), approximately 2.5% of whom identified as transgender. Transgender boys had a higher prevalence suicidal ideation than cisgender boys (APR = 2.97; 95% CI = 1.89, 4.67) and cisgender girls (APR = 2.29; 95% CI = 1.55, 3.40). Transgender girls were less likely than cisgender boys and girls to be ever drinkers, while transgender boys were more likely than cisgender boys and girls to be ever drinkers. Transgender girls had higher past-year exposure to sexual violence than cisgender boys (APR = 2.74; 95% CI = 1.52, 4.95) and cisgender girls (APR = 4.93; 95% CI = 2.52, 9.67). Conclusion We found disparities in behavioral health and experience of violence between transgender and cisgender adolescents in Thailand. The findings highlighted the need for program managers and policy makers to consider expanding local efforts to address health gaps in the LGBTQ community to also include school-going youth population.